Strategi Kantor Urusan Agama Anjir Pasar Menekan Angka Perkawinan Anak dalam Mencapai SDGs 5 : Strategy of The Anjir Pasar Office of Religious Affairs to Reduce Child Marriage Rates Towards SDGs 5 - Fitriani Sari, Devi; Falikhah, Nur; Yani Gusriani, Raden (Jurnal Bimas Islam, 2024)
Sustainable Development Goals (SDGs) are a global and national commitment that aims to improve society's welfare, including 17 goals. One of them is gender equality, which is target number 5. The fifth goal in the 2030 SDGs concerns women aged 20-24 years who married before 18 years at 8.74%. Meanwhile, 10.53% of women aged 20-24 were married before 18 years in South Kalimantan province. This empirical fact shows that South Kalimantan Province still has to work hard to reduce the rate of child marriage. This is field research with data collection, namely observation, interviews, and documentaries. The research results show that a strategy to accelerate the reduction of child marriage is needed. The Anjir Pasar, Religious Affairs Office, implements several strategies to reduce the number of child marriages in achieving SDG 5 (gender equality), including collaboration with several parties in the Marriage Age Maturation (PUP) program, time-gaining strategies, skills training, providing rejection letters, education and outreach. Outreach to Islamic boarding schools can be one of the keys to suppressing child marriage, considering that the people of South Kalimantan are a religious community, obedient to the messages conveyed by Tuan Guru in their respective regions.